The EU democracy policy in Latin America: narrative and funding - Povse, Max; Chaguaceda Noriega, Armando (Frontiers in Political Science, 2024)
Democracy is a central concern in the EU narrative toward Latin America; still, the allocation of funds does not follow this narrative closely, resulting in a chronic lack of support for local CSOs. The allocated funds face misappropriation by local authorities and the indirect support of low- and non-democratic regimes, reflected in the affected countries’ drop in indices that measure Social Progress and Democracy. This situation is further aggravated by prioritizing projects that reflect EU-centered agendas and skew the critical aid needed for democracy resilience building. As a response, we bring forward recommendations for the EU to bridge the gap between its democracy policy narrative and execution in Latin America, focusing on the particular needs of the region’s democratic agents.